2009
DOI: 10.1021/jp9065339
|View full text |Cite
|
Sign up to set email alerts
|

Surface Temperature Dependence of Methane Activation on Ni(111)

Abstract: Vibrational state resolved measurements of methane’s dissociation on Ni(111) show a strong surface temperature dependence near the translational energy threshold for reaction. The reactivity of molecules excited to v = 1 of the ν3 C−H stretching vibration and incident on the surface with a translational energy of 40 kJ mol−1 increased 8-fold as the surface temperature increased from 90 to 475 K. This enhancement is much larger than that reported for earlier studies at higher incident energies. These results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 46 publications
4
44
0
Order By: Relevance
“…For the laser-off measurements, the sticking coefficient for T S = 500 K is lower for E trans less than 90 kJ/mol, whereas increasing T S at higher energies does not change S laser-off 0 significantly. This is consistent with previous experiments performed by Utz et al for the dissociative chemisorption of CH 4 on Ni(111), 22,25 where it was found that S ν 3 0 increased more as T S was increased when the total energy (E trans + E vib ) was lower than the barrier height, and S ν 3 0 changed less when the total energy was greater than the barrier height.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For the laser-off measurements, the sticking coefficient for T S = 500 K is lower for E trans less than 90 kJ/mol, whereas increasing T S at higher energies does not change S laser-off 0 significantly. This is consistent with previous experiments performed by Utz et al for the dissociative chemisorption of CH 4 on Ni(111), 22,25 where it was found that S ν 3 0 increased more as T S was increased when the total energy (E trans + E vib ) was lower than the barrier height, and S ν 3 0 changed less when the total energy was greater than the barrier height.…”
Section: Resultssupporting
confidence: 93%
“…[15][16][17][18][19][20][21][22] Several techniques have been developed to measure sticking coefficients with quantum state resolution, for example, by detecting the surface bound products using Auger electron spectroscopy, 5,6,23,24 reflection absorption infrared spectroscopy, 7,11,15,21 or titration of the adsorbates to make molecules that desorb and can be detected in the gas phase mass spectrometrically. 9,12,22,25 Whilst these have proved to be powerful techniques for determining quantum state resolved sticking coefficients, they share a common disadvantage in that calibrations are necessary to quantify the adsorbate coverage and number of molecules incident on the surface, both of which need to be known to accurately determine the sticking coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…36,37,40,74,75 Another simulation suggests any enhancement of the reaction rate via phonons diminishes with increasing translational or vibrational energy of the incident methane. 76 Recent experimental results support this theory 77 and we plan to explore the role of phonon excitation on methane activation more fully in a future publication. Inelastic tunnelling 11,44,78 or infrared excitation studies of surface-adsorbed species 79 differ in some ways from the beamsurface studies highlighted above, but key features of this framework still apply.…”
Section: Impact Of Ivr On Surface Reactivity and Dynamicsmentioning
confidence: 75%
“…[1][2][3] The outline of the review is as follows. The first section introduces key concepts and definitions that are used when discussing gas-surface reaction dynamics.…”
Section: Introductionmentioning
confidence: 99%